If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = z + -18 Reorder the terms: -3 = -18 + z Solving -3 = -18 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. -3 + -1z = -18 + z + -1z Combine like terms: z + -1z = 0 -3 + -1z = -18 + 0 -3 + -1z = -18 Add '3' to each side of the equation. -3 + 3 + -1z = -18 + 3 Combine like terms: -3 + 3 = 0 0 + -1z = -18 + 3 -1z = -18 + 3 Combine like terms: -18 + 3 = -15 -1z = -15 Divide each side by '-1'. z = 15 Simplifying z = 15
| 30+3*x-2*(12-x)=38 | | 10-2m=m+4 | | 8y-7=14y+23 | | 4x+12=38 | | -6x^2=-35 | | 10/62 | | 9x-7=6x+38 | | 50=x-15 | | 27x+901= | | 8x-3=5x-57 | | n/4-5=17 | | 5(x+6)-(x+28)=-2x | | f(x)=x-9/X^2-16 | | 8x+2=6x+36 | | 8(3x-4)=14x-2 | | 17x-9x=24 | | 5x-(2x+9)=9 | | -97x+42x= | | 6(7x-6)=27 | | 15-6x=-51 | | c+1.7=2.6 | | 96-3x=8 | | -6i+4= | | 6x-17=-107 | | 5(x-6)-(x+28)=-2x | | (x-3+5i)(x-3-5i)=0 | | 420=(2x+5)x | | 3(5-2m)=27 | | 798x+2(60)=500x | | 3.4+t=10.5 | | 5x+15=3+7x-8 | | 3y+9y=21 |